Slide origin of breccia lenses in the Cambrian of the North China Platform: new insight into mass transport in an epeiric sea - van Loon, A.J. (Tom); Han, Zuozhen; Han, Yu (Geologos, 2012)
An oolite in the Furongian (Late Cambrian) Chaomidian Formation in Shandong Province, China, which was deposited on the North China Platform in an epeiric sea, contains several limestone breccia lenses of various dimensions (centimetres to decimetres thick and decimetres to more than 10 metres in length) in an E-trending section. The oolite, which is approximately 40 cm thick, was originally thicker, as indicated by a planar truncation surface that formed by wave abrasion. The breccia lenses in this oolite are generally mound-shaped with a flat base and a convex top. The western margin of the lenses is commonly rounded whereas the eastern margin commonly has a tail (consisting of a rapidly eastwards thinning breccia horizon that gradually ends in a horizon of isolated clasts). Some of the breccia lenses are underlain by a shear zone. The formation of the breccia lenses cannot be easily explained by normal depositional or deformational processes. It is concluded that the lenses represent fragments of a partly consolidated layer, consisting of both rounded and angular platy clasts, which slid down over a very gently inclined sedimentary surface which acted – possibly together with a water film – as a lubricant layer. During transport, the layer broke up into several discrete bodies that formed small ‘highs’ at the sedimentary surface of the shallow epeiric sea. Subsequently, waves partially eroded the lenses, mostly at their margins, producing their mound-shaped form. Sliding of blocks is known from a wide variety of environments in the sedimentary record; however, this is the first description of the sliding of blocks in an epeiric sea. This indicates that such a low-relief submarine carbonate setting is, like its siliciclastic counterparts, susceptible to this process.